Weed Control with Accent, Callisto, Isoxadifen, Impact, Cinch, Dicamba, and Atrazine in Irrigated Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Some timings and combinations of the herbicides tested in this study controlled Palmer amaranth, kochia, quinoa, Russian thistle, and green foxtail from 95 to 100% 51 days after postemergence application (DA-B). Accent (nicosulfuron) plus Callisto (mesotrione) and isoxadifen alone postemergence provided 88% Palmer amaranth control at 51 DA-B. Kochia control was 92 and 90% when Accent plus Callisto and isoxadifen alone or with atrazine and Dicamba XP (dicamba) was applied postemergence following Cinch (S-metolachlor) preemergence application. Crabgrass control with preemergence followed by postemergence treatments exceeded 89%. Crabgrass control was 83 and 88% when no preemergence herbicide was applied prior to postemergence herbicides. No herbicide treatment increased corn yield relative to the untreated controls.
Keywords: irrigated corn; weed control; Palmer amaranth; kochia; quinoa; Russian thistle; green foxtail; Callisto; Mesotrione; Accent; Nicosulfuron; Isoxadifen; Impact; Topramezone; Cinch; S-metolachlor; Dicamba; Atrazine